Single-bit modulator for wireless power transfer system - Dhafer Almakhles; Akshya Swain; Umashankar Subramaniam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper proposes a single-bit ADC system based Proportional and Integral (PI) controller to maintain a desired level of power transfer efficiency in Capacitive Power Transfer (CPT) systems. In this paper, a simple single-bit ADC system i.e., Single-Bit Modulator (SBM) is considered as an alternative to the commonly used multi-bit ADC systems. Unique features of employing SBM are 1) its ability to convert analog signals into single-bit signals and 2) its easy integrability in digital chips with linear variable differential transformers (LVDTs) such as FPGAs. A SBM based PI (SBM-PI) controller is designed to judicially interface with the single-bit output of SBM. The proposed (SBM-PI) controller guarantees less hardware resources, latency and regulates the output voltage to provide the desired power transfer efficiency. The behavior of SBM-PI controller is compared to that of a conventional multi-bit controller, with the results of both controllers being identical. The effectiveness of the proposed controller with SBM is further demonstrated using the experimental prototype of CPT by implementing a SBM-PI controller using $16$ MHz ATmega8 microcontroller. The experimental results from a laboratory prototype illustrate that SBM-PI controller successfully regulates the output voltage of CPT to control the power flow.